Growth and yield of yellow passion fruit under hydrogel and vegetal mulching doses - Brasil, Brasil; Brasil, Brasil; Brasil, Brasil; Henrique Maciel Carvalho, Lucas; Brasil, Brasil; Brasil, Brasil; Brasil, Brasil; Brasil, Brasil (Comunicata Scientiae, 2025)
The yellow passion fruit is one of the most widely cultivated fruit crops in Brazil, with the Northeast region being particularly prominent. Despite being the largest national producer, water scarcity remains the primary limiting factor for expanding this crop in Brazilian semi-arid regions. Given this challenge, there is a need for soil management techniques that enhance water use efficiency by plants. This study aimed to evaluate the growth and production components of yellow passion fruit in soil treated with hydrogel and mulching from crop residues. The experiment was conducted using a randomized block design in a 5 × 2 factorial arrangement, corresponding to five hydrogel doses (0, 0.5, 1.0, 1.5, and 2.0 g dm⁻³ of soil) in soil with and without mulching derived from Brachiaria plant residues. The analyzed variables included plant height, stem diameter, number of branches and leaves, number of fruits, yield per plant, average fruit mass, and yield. Yellow passion fruit growth was enhanced with a hydrogel dose of 1.1 g dm⁻³, and yield improved with doses ranging from 0.65 to 2.0 g dm⁻³ in the second harvest. Soil with mulching from Brachiaria plant residues increased the yield of yellow passion fruit, particularly in the second harvest.